2016
DOI: 10.1080/03004430.2016.1223061
|View full text |Cite
|
Sign up to set email alerts
|

Children’s engagement in play at home: a parent’s role in supporting play opportunities during early childhood

Abstract: J.L. (2016). Children's engagement in play at home: A parent's role in supporting play opportunities during early childhood. Early Child Development and Care, 187(5-6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 26 publications
2
18
0
2
Order By: Relevance
“…Currently there are also investigations demonstrating a positive association among parental play beliefs, children's play skills and developmental outcomes. For instance, studies found that parents' play support beliefs were positively associated with their children's interactive play skills (Fogle and Mendez, 2006;LaForett and Mendez, 2016), while parents' academic focused beliefs were negatively associated with the same set of skills (LaForett and Mendez, 2016). An investigation by Lin and Yawkey (2014) indicated that parental play beliefs were associated with children's social skills even after controlling for the parental background variables associated with children's social competence.…”
Section: Parental Play Beliefs Children's Play Experiences and Develmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently there are also investigations demonstrating a positive association among parental play beliefs, children's play skills and developmental outcomes. For instance, studies found that parents' play support beliefs were positively associated with their children's interactive play skills (Fogle and Mendez, 2006;LaForett and Mendez, 2016), while parents' academic focused beliefs were negatively associated with the same set of skills (LaForett and Mendez, 2016). An investigation by Lin and Yawkey (2014) indicated that parental play beliefs were associated with children's social skills even after controlling for the parental background variables associated with children's social competence.…”
Section: Parental Play Beliefs Children's Play Experiences and Develmentioning
confidence: 99%
“…Play is a naturally occurring activity that offers children important developmental benefits (LaForett and Mendez, 2016). According to early theories of child development, play is a primary source of learning beyond being a means to healthy social-emotional development (see Piaget, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian [18] menjelaskan bahwa bermain peran adalah hal yang menyenangkan bagi anak karena anak dapat berinteraksi dengan teman sebayanya serta dapat mengeksplorasi perasaannya dan memahami perasaan orang lain oleh karena dengan adanya interaksi maka bermain peran dapat meningkatkan keterampilan berbicara anak. Selain itu penelitian yang dilakukan oleh [19] menjelaskan bahwa bermain peran dapat menambah pengalaman bagi anak dan dapat mengurangi pengalaman buruk yang di alami anak atau trauma anak juga bermain peran dapat meningkatkan keterampilan anak dalam berbicara [20].…”
Section: Pengaruh Metode Role Play Terhadap Keterampilan Berbicara Anunclassified
“…One of the possible explanations for this cross-cultural variation could be linked to the nature and structure of the play opportunities and activities parents recurrently facilitate for their children at home. Concerning this point, based on their interpretation of the findings from parental belief studies, LaForett and Mendez (2016) underlined that parents' play beliefs could affect the nature of play activities their children frequently engage in. For instance, many of the play activities that Hungarian parents facilitate for their children in their everyday lives could involve the use of shifting skills on top of inhibitory control skills compared to their Ethiopian counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…These opportunities in turn seem to create better developmental opportunities for children (Thorp et al, 1995;Carson and Parke, 1996;O'brien and Md-Yunus, 2007;Lin and Yawkey, 2014). Thus, investigating parental play beliefs, the level of involvement in their children's play and children's play experiences at home are important issues to be examined in relation to children's developmental outcomes (LaForett and Mendez, 2016).…”
Section: Play and Child Developmentmentioning
confidence: 99%